PRODUCTION OPTIMIZATION IN ZURI GAS FIELD WITH TYPE CARBONATE RESERVOIR - AGUNG GDE ISWARA ANINDYAJATI, ANAK
The Zuri gas field was discovered in 1972 by drilling a Z-3 exploration well that penetrated Peutu carbonate reservoir. The field is in the process of developing gas projects to fulfill the gas sales commitment to PT Pertamina (Persero). During the 2017-2018 period, three new wells have been drilled, namely Z-9A, Z-11 and Z-12. The well tests (Modified Isochronal Test and Pressure Build-Up) were carried out on the three wells. The well testing data is analyzed and the results are used to form the Inflow Performance Relationship (IPR) and Vertical Lift Performance (VLP). Multi tank reservoir models with MBAL software are used to determine the production of the Zuri gas field with the characteristics of heterogeneous carbonate reservoirs. In this field, each tank is assumed not to relate to one another. Next, the evaluation was conducted to determine the production of the Zuri gas field with several scenarios of adding new wells in order to maintain the production plateau in accordance with the gas sales commitment. Vertical Lift Performance of the new well uses a model of well that already exists in each tank that is adjusted to the geometry of the new well. The best scenario is chosen based on technical and economic evaluation considering the existing and/or applicable constraints on the Zuri gas field.